The Swiss occupational pension system - Nussbaum, Werner (Henry Stewart Talks, 2012)
Facts and figures about the Swiss pension system, Mandatory and extra-mandatory pension plans, Coordination of the different pillars (paygo, funded) within a multi-pillar-approach in regard of income replacement, General trends with respect to the contributors/beneficiaries-ratio, Shifting from defined benefit to defined contribution plans, Pension asset investment rules, principles and facts, Comparison with other countries with respect to the meaning of the different pillars within a multi-pillar-pension system
Updated at 2013/07/17